Avaliação da ocorrência do Diabetes Mellitus tipo 1 entre 0 e 18 anos de idade e associação de eventos com o desenvolvimento precoce da doença - Tatiana de Oliveira Rassi (2016)
Type 1 Diabetes (DM1) is one of the most common chronic diseases in childhood and it´s frequency varies among different populations. In the last thirty years, the incidence of DM1 has increased worldwide. Brazil that was once classified as a country with intermediate incidence, has revealed high incidence rates in the last decade (27,2/100.000 hab). In many countries, the increase of DM1 was more noticeable in the age group between 0 and 4 years old. Genetic and environmental factors may be involved in the pathogenesis of the disease and possibly with itsincrease. The aim of this study was to evaluate the temporal trend of newly diagnosed DM1 cases in a Brazilian pediatric endocrinology service, its distribution according to age and the relationship between age of diagnosis and early life events. Data was obtained from thePediatric Diabetes Group of the Federal University of Minas Gerais University Hospital (HCUFMG). Information about: the diagnosis, perinatal factors, first-year feeding and socioeconomic status were collected through a standardized questionnaire. Six hundred andsixty-three children diagnosed with DM1 attended the University hospital between 1969 and 2015. Temporal trends were analyzed between 1980 and 2014 with 642 children, who were divided into three groups according to age at diagnosis ( 4y, 5-9y and 10y). The studiedperiod was divided in 5-year intervals: 1980-1984, 1985-1989, 1990-1994, 1995-1999, 2000- 2004, 2005-2009 and 2010-2014. There was a progressive decrease in the proportion of children diagnosed between 0 and 4 years old (47% in 1990-1994 to 20 % in 2010-2014; p=0,01) and an increase in the proportion of children diagnosed after 10 years old (13% in 1990-1994 to 54% in 2010-2014; p=0,01). There was no statistical difference between the proportion of children diagnosed between 5 and 9 years old through the studied time. In the studied population the diagnosis of DM1 in infants and toddlers seems to be decreasing throughout the years while in the age group older than 10 years, it seems to be increasing. Although data are inadequate toestimate the true incidence of DM1 in children in the city of Belo Horizonte, it should be noticed that this University hospital is one of the main regional public reference center for specialized care of children with DM1. Therefore, it is intriguing to verify the reasons of these results compared to the literature. Analyzing early life events, in 136 children there was an association of DM1 in younger age with the introduction of gluten after 6 months old (OR: 2,27 CI 95%: 1,12-4,58 p= 0,02). In another analysis with 283 patients, an association was observed between DM1 before 5 years old and a higher number of family members living at the same house at the time of diagnosis (OR: 2,41 CI 95%: 1,45-3,98 p<0,001). The Acceleration Theory could explain this finding, as it was shown a higher prevalence of younger children diagnosed with DM1 in families living in worse sanitary conditions. However, more studies should be performed to confirm and clarify this information.